Specific pattern of maturation and differentiation in the formation of cortical tubers in tuberous sclerosis omplex (TSC): evidence from layer-specific marker expression. Issue 1 (December 2016) - Mühlebner, Angelika; Iyer, Anand; van Scheppingen, Jackelien; Anink, Jasper; Jansen, Floor; Veersema, Tim; Braun, Kees; Spliet, Wim; van Hecke, Wim; Söylemezoğlu, Figen; Feucht, Martha; Krsek, Pavel; et al.
Abstract Background Tuberous sclerosis complex (TSC) is a multisystem disorder that results from mutations in the TSC1 or TSC2 genes, leading to constitutive activation of the mammalian target of rapamycin (mTOR) signaling pathway. Cortical tubers represent typical lesions of the central nervous system (CNS) in TSC. The pattern of cortical layering disruption observed in brain tissue of TSC patients is not yet fully understood, and little is known about the origin and phenotype of individual abnormal cell types recognized in tubers. Methods In the present study, we aimed to characterize dysmorphic neurons (DNs) and giant cells (GCs) of cortical tubers using neocortical layer-specific markers (NeuN, SMI32, Tbr1, Satb2, Cux2, ER81, andRORβ ) and to compare the features with the histo-morphologically similar focal cortical dysplasia (FCD) type IIb. We studied a cohort of nine surgically resected cortical tubers, five FCD type IIb, and four control samples using immunohistochemistry and in situ hybridization. Results Cortical tuber displayed a prominent cell loss in all cortical layers. Moreover, we observed altered proportions of layer-specific markers within the dysplastic region. DNs, in both tubers and FCD type IIb, were found positive for different cortical layer markers, regardless of their laminar location, and their immunophenotype resembles that of cortical projection neurons. Conclusions These findings demonstrate that, similar to FCD type IIb, cortical layering is markedly disturbed in cortical tubers of TSC patients. Distribution of these disturbances is comparable in all tubers and suggests a dysmaturation affecting early and late migratory patterns, with a more severe impairment of the late stage of maturation.